Migrant remittance flows : findings from a global survey of central banks / Jacqueline Irving, Sanket Mohapatra, Dilip Ratha. - Irving, Jacqueline (World Bank working paper, 2010)
Drawing on the findings from responses to a survey conducted in 2008-09 from 114 central banks worldwide (of which 33 are in Africa), Migrant Remittance Flows aims to better understand how central banks and other national institutions regulate and collect data and other information on cross-border remittance flows. Findings indicate that, although the vast majority of countries, in both sending and receiving countries, collect data on remittances, and 43 percent of receiving countries estimate informal remittances, there is a need for more frequent and better coordinated data collection, both.